1973
DOI: 10.1016/0008-8749(73)90020-8
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte in vitro cytotoxicity: Mechanism of human lymphotoxin-induced target cell destruction

Abstract: These in. vitro studies were conducted in an attempt to elucidate the mechanism of how cell-free supernatant fluids obtained from PHA-stimulated human lymphocytes cause destruction of cells. The undiluted supernatant fluids with high activity exerted a nonspecific cytotoxic effect on many different continuous cell lines. However, upon dilution, a wide spectrum of cell sensitivities was observed. These studies suggest human lymphotoxin acts by first absorbing to receptors on the target cell plasma membrane. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1974
1974
1988
1988

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Among these target cells, one of the most susceptible cells was L cells. Cell destruction by lymphotoxin occurred in 36 to 48 hr (20). These biological properties were very similar to those of cytotoxin reported in the present paper.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among these target cells, one of the most susceptible cells was L cells. Cell destruction by lymphotoxin occurred in 36 to 48 hr (20). These biological properties were very similar to those of cytotoxin reported in the present paper.…”
Section: Discussionsupporting
confidence: 90%
“…Lymphotoxin activity was found in culture supernatants of PHA-stimulated lymphocytes obtained from many kinds of animal species (19). One of the most remarkable properties of mouse lymphotoxin was that it exhibited nonspecific cy-totoxic effects on a wide variety of cells derived from many kinds of animal species, either continuous cell lines such as L and HeLa cells or primary cell cultures such as mouse and chicken embryonic fibroblasts, or red blood cells (20). Among these target cells, one of the most susceptible cells was L cells.…”
Section: Discussionmentioning
confidence: 99%
“…These substances are known to have a wide range of effects upon other cells in vitro (15)(16). One of these molecules has been termed "lymphotoxin" (LT), an apparently nonspecific cell toxin, having a diverse range of cytolytic activity on different cell types in vitro (17,18). Lymphotoxin has been detected in culture supernatants from lymphocytes activated by mitogens, antigens, and in mixed leukocyte reactions (19,20).…”
Section: 52mentioning
confidence: 99%
“…The observed direct cell-to-cell interaction might facilitate lymphotoxin activity against the plasma membrane as discussed by Williams and Granger (1969). These authors and Russell et al (1972) found that high concentrations of lymphotoxin are reqtiiied to achieve cytolysis.…”
Section: Discussionmentioning
confidence: 92%